House price dynamics in the wake of the Tax Cuts and Jobs Act of 2017; Dinámica de los precios de la vivienda a raíz de la Ley de Empleos y Reducción de Impuestos de 2017 - John Anderson (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2024)
The Tax Cuts and Jobs Act of 2017 (TCJA) changed tax policy in two important aspects. It limited state and local tax deductions (SALT) to 10,000 and lowered marginal tax rates in most income brackets. In this analysis, I estimate house price time series models for 20 U.S. cities using Case-Shiller data and test for series breaks when TCJA was adopted and implemented. The purpose is to test whether there is a unit root with breakpoints in each series. If so, the TCJA shock was permanent, not transitory, and the time series process is not mean reverting. Results reveal significant breaks in 12 of the 20 city indices. Additionally, there are significant breakpoints in 22 of the 48 tests across city price tiers (16 cities with three house price tiers each). The modal break date is the month of TCJA legislation passage with another 13 significant breakpoints within six months of TCJA adoption. Results indicate that TCJA was associated with an initial negative effect on house prices in many housing markets and price tiers. Importantly, the presence of unit root processes indicates that house price dynamics are more variable subsequently.
Keywords: H31; R31; C22; 330; House price dynamics; tax cuts; event study